1988
DOI: 10.1111/j.1464-410x.1988.tb04324.x
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal Ultrasound versus Cystography In the Evaluation of Anatomical Stress Urinary Incontinence

Abstract: Thirty-two female patients with clinical and urodynamic findings of genuine stress urinary incontinence were evaluated before and 6 months after surgery for stress urinary incontinence. Twenty-nine control patients had identical evaluations before and 6 months after surgery which did not involve the urethrovesical junction. Twenty-four patients with primary bladder instability had similar evaluations and served as a second control group. Anatomical landmarks indicating support to the urethrovesical junction we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2
6

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 21 publications
5
43
2
6
Order By: Relevance
“…This displacement under stress happens to both continent and incontinent women; the difference between them is that incontinent women not only start from worse rest conditions but also have a greater displacement, with the subsequent failure of continence mechanisms. Nevertheless, it was already reported that changes in the bladder neck position are significantly different in continent and incontinent women [2,17,22,[24][25][26][27]. The results of the present study show that when straining, either on a Valsalva manoeuvre or, more exaggerated, during coughing, the US variables in continent women tend to approach values that suggest UI.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This displacement under stress happens to both continent and incontinent women; the difference between them is that incontinent women not only start from worse rest conditions but also have a greater displacement, with the subsequent failure of continence mechanisms. Nevertheless, it was already reported that changes in the bladder neck position are significantly different in continent and incontinent women [2,17,22,[24][25][26][27]. The results of the present study show that when straining, either on a Valsalva manoeuvre or, more exaggerated, during coughing, the US variables in continent women tend to approach values that suggest UI.…”
Section: Discussionsupporting
confidence: 54%
“…As an anatomical defect constitutes the basis for this dysfunction, identifying this defect would result in a better approach to treatment [1]. Many imaging techniques have been used to register the changes occurring in the urethra during stress, but ultrasonography (US) seems to have major advantages over other procedures; it is feasible, cheap, it does not involve ionizing radiation and provides at least the same amount of accurate information [2][3][4]. Moreover, US offers other possibilities, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…98,143,144 The data from these studies were combined to provide a pooled sensitivity of 0.84 (95% CI 0.76 to 0.90) and specificity of 0.86 (95% CI 0.79 to 0.91). The positive likelihood ratio associated with the pooled sensitivity and specificity is 6 (95% CI 4.72 to 7.28) and the AUC for the ROC curve corresponding to the pooled DOR is 0.94 (95% CI 0.84 to 1.00) (Figure 9).…”
Section: Imaging Techniques Compared With Multichannel Urodynamicsmentioning
confidence: 99%
“…143,144 A urethrovesical junction drop during stress of at least 1 cm was defined as the cut-off for USI. and transperineal 98,140 ) with fluoroscopy during videourodynamics.…”
Section: Urodynamics Compared With Ultrasoundmentioning
confidence: 99%
“…Bu çal›flmalar›n verileri bir havuzda birlikte de¤erlendirildi¤i zaman duyarl›l›¤› 0,84 ve özgüllü¤ü 0,86 olarak saptanm›flt›r (5,(52)(53)(54) .…”
Section: üRodinami Ile Test Gruplar›n›n Karfl›laflt›r›lmas›unclassified